Trapping of electrons in metal oxide-polymer memory diodes in the initial stage of electroforming - Bory, Benjamin F. (2014)
Metal oxide-polymer diodes require electroforming before they act as nonvolatile resistive switching memory diodes. Here we investigate the early stages of the electroforming process in Al/Al2O3 /polyspirofluorene /Ba/Al diodes using quasistatic capacitance-voltage measurements. In the initial stage, electrons are injected into the polymer and then deeply trapped near the polyspirofluorene-Al2O3 interface. For bias voltages below 6 V, the number of trapped electrons is found to be CoxideV/q with Coxide as the geometrical capacitance of the oxide layer. This implies a density of traps for the electrons at the polymer-metal oxide interface larger than 31017 m−2.